Does Financial Openness Affect Economic Growth in Asian Economies? A Case Study in Selected Asian Economies, 1980-2010 - Hsinrong P. Wei (Journal of Economics and Political Economy, 2014)
In recent decades, financial liberalization has been one of the most important strategies for Asian countries to promote growth. However, debate emerges following several financial crises on whether liberalizing financial markets and allowing for free access to international capital markets, would benefit or impede economic development. The objective of this study is to examine the impact of financial openness on select seventeen Asian economies and answer the three questions: 1. Is there any linkage between financial openness and economic growth for these seventeen Asian countries? 2. Does any of the financial openness pose positive or negative effects? 3. If no direct impact revealed, can financial openness still have growth effect under certain fundamental or institutional conditions? Our main findings are as follows: 1. By employing both de jure and de facto indicators of financial openness, our empirical results indicate that the de facto indicators are associated with growth of Asian economies but de jure indicator does not show statistically significant impact on growth across three methodologies. 2.Furthermore, these growth effects vary among the de facto indicators. According to our empirical results, out of the four de facto financial openness measurements, only one of them, foreign direct investment inflows, influences growth positively whereas three other measures, including foreign direct investment outflows, portfolio investment inflows and outflows exert negative impact on growth. In terms of the view that the growth effect of the financial openness depends on macroeconomic foundations or institutional conditions of an economy, our findings do not support this view due to the estimation results are not robust across five financial openness proxies.
Keywords: F20; F21; F43; 330; Financial Openness; Inward FDI; Outward FDI; Portfolio Assets; Portfolio Liabilities